Angleški končni -e in slovenski pravopis - Ilc, Gašper (Jezik in slovstvo, 2004)
The article discusses some aspects of Slovene orthography related to the (non-)omission of the word-final mute -e in the Slovene declination of Englishproper nouns (cf. Slovenski pravopis 2001, 772). It shows that the existing rule fails to cover all phonological properties of mute -e, which is reflected in the inconsistent spelling of English nouns in Slovene oblique cases. The discussion reveals the need to modify the existing orthography rule(s), perhaps in a manner that would allow for the general (non-)omission of the word-final mute -e.
Keywords: Slovene; slovenščina; angleščina; English; orthography; pravopis; Slovenski pravopis; pragmatika